Strategi Manajemen Travel Smarts Umrah Dalam Meningkatkan Jamaah Umrah Di Palembang - Robayadi Robayadi; Candra Darmawan (Social Science and Contemporary Issues Journal, 2023)
ABSTRACT: This thesis is entitled "Travel Smarts Umrah Management Strategy in Increasing Pilgrims Umrah in Palembang." This research is about how the travel smarts umrah management strategy in increasing pilgrims in the city of Palembang. The purpose of this study was to examine and find out the management strategies used by Travel Smarts Umrah Palembang and the inhibiting factors in implementing management strategies to increase pilgrims. This study uses qualitative methods by conducting field research, using management strategy theory according to Riva'i namely strategy formulation, strategy implementation, evaluation. Data collection techniques used are observation, interviews, documentation. The results of the analysis concluded that the management strategy used by Travel Smarts Umrah Palembang designed a strategic activity by promoting it through social media, prepaid advertisements, broadcasting to places of recitation, distributing brochures, submitting proposals to government agencies and company strategies that were implemented quite well. While the inhibiting factor of the strategy used is the first is the use of artist figures, because travel parties have difficulty paying and cannot be used continuously to use artists as public figures in attracting public interest. Second, there are many companies or agencies that are not interested in working with travel smarts Umrah, because some governments and agencies carry out the Umrah pilgrimage individually, not through a company.